1994
DOI: 10.1152/ajpheart.1994.266.3.h854
|View full text |Cite
|
Sign up to set email alerts
|

In vivo detection of endogenous acetylcholine release in cat ventricles

Abstract: To detect and monitor endogenous acetylcholine (ACh) release in the in vivo heart, we applied a dialysis technique to the hearts of anesthetized cats. Dialysis probes were implanted in the left ventricular myocardium and were perfused with Krebs-Henseleit solution containing Eserine (10(-4) M) at 3 microliters/min. Dialysate ACh concentration was measured with high-performance liquid chromatography. In four cats, the response to vagal stimulation was studied. Electrical stimulation of efferent vagal nerves (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 0 publications
2
50
0
Order By: Relevance
“…A cardiac microdialysis is a powerful tool to estimate neurotransmitter levels in the myocardial interstitium in vivo (2,3,14,19,20,31). The present study demonstrated that hypothermia significantly attenuated the myocardial interstitial releases of NE and ACh in the ischemic region during the LAD occlusion.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…A cardiac microdialysis is a powerful tool to estimate neurotransmitter levels in the myocardial interstitium in vivo (2,3,14,19,20,31). The present study demonstrated that hypothermia significantly attenuated the myocardial interstitial releases of NE and ACh in the ischemic region during the LAD occlusion.…”
Section: Discussionsupporting
confidence: 55%
“…The materials and properties of the dialysis probe have been described previously (2,3). Briefly, we designed a transverse dialysis probe.…”
Section: Dialysis Techniquementioning
confidence: 99%
“…Accordingly, whether ANG II affects the vagal control over the ventricle remains unknown. The aim of the present study was to examine the effect of ANG II on the vagal stimulation-induced ACh release in the left ventricular myocardium by measuring the interstitial ACh levels directly using a cardiac microdialysis technique (1,(13)(14)(15). We also explored the possible sites of action for the effect of ANG II on the stimulation-induced ACh release by administering losartan systemically from the femoral vein or locally through the dialysis fiber.…”
mentioning
confidence: 99%
“…We measured the concentration of ACh in the dialysate sample as an index of myocardial interstitial ACh level (10)(11)(12)(13). Materials and properties of the dialysis probe have been reported previously (2). Briefly, we designed a transverse dialysis probe.…”
Section: Methodsmentioning
confidence: 99%
“…We have measured myocardial interstitial acetylcholine (ACh) levels by using a cardiac microdialysis technique in anesthetized cats (2,(10)(11)(12)(13). The ACh levels measured by the cardiac microdialysis were able to detect changes in the ACh kinetics in the vagal nerve terminals induced by pharmacological interventions, arterial baroreflex, or Bezold-Jarisch reflex (13).…”
mentioning
confidence: 99%